Place crowd safety, crowd science? Case studies and application. Issue 4 (15th April 2020) - Still, Keith; Papalexi, Marina; Fan, Yiyi; Bamford, David
Abstract : Purpose: This paper aims to explore the development and application of place crowd safety management tools for areas of public assembly and major events, from a practitioner perspective. Design/methodology/approach: The crowd safety risk assessment model is known as design, information, management-ingress, circulation, egress (DIM-ICE) (Still, 2009) is implemented to optimise crowd safety and potentially throughput. Three contrasting case studies represent examples of some of the world's largest and most challenging crowd safety projects. Findings: The paper provides some insight into how the DIM-ICE model can be used to aid strategic planning at major events, assess potential crowd risks and to avoid potential crowd safety issues. Practical implications: It provides further clarity to what effective place management practice is. Evidence-based on the case studies demonstrates that the application of the DIM-ICE model is useful for recognising potential place crowd safety issues and identifying areas for require improvement. Originality/value: Crowd science is an emerging field of research, which is primarily motivated by place crowd safety issues in congested places; the application and reporting of an evidence-based model (i.e. DIM-ICE model) add to this. The paper addresses a research gap related to the implementation of analytic tools in characterising place crowd dynamics.